Facile Non‐Transition Metal‐Catalyzed Synthesis of 2‐Thioxo‐2, 3‐dihydroquinazolin‐4(1H)‐one Derivatives via One‐Pot Multicomponent Reactions. Issue 1 (3rd January 2019) - Bahadorikhalili, Saeed; Rahimzadeh, Golnaz; Kianmehr, Ebrahim; Ansari, Samira; Hamedifar, Haleh; Mahdavi, Mohammad
Abstract: In this paper, a novel method is introduced for the synthesis of 3‐substituted 2‐thioxo‐2, 3‐dihydroquinazolin‐4(1 H )‐one derivatives. This methodology is based on the multicomponent one‐pot reaction of isatoic anhydride, amines, chloroform and sulfur in basic conditions. The products are obtained in highest efficiency when the reaction is performed in 1, 4‐dioxane as the solvent in the presence of potassium tert ‐butoxide as the base. The reaction showes to be efficient and simple for the preparation of these compounds. In addition, this method is general and different aromatic or aliphatic amines are used and the desired products are isolated in high yields. A possible mechanism for the reaction is proposed, which consisted the dichlorocarbene formation under the basic conditions. Abstract : In this paper, a novel method is introduced for the synthesis of 3‐substituted 2‐thioxo‐2, 3‐dihydroquinazolin‐4(1 H )‐one derivatives, based on the multicomponent one‐pot reaction of isatoic anhydride, amines, chloroform and sulfur in basic conditions. The optimal reaction condition is 1, 4‐dioxane solvent in the presence of potassium tert ‐butoxide base. This is a general method and different aromatic or aliphatic amines can successfully be used. A possible mechanism for the reaction is suggested, which consists in the dichlorocarbene formation under basic conditions.